Meneladani Sejarah Pendidikan Islam di Kesultanan Aceh - Guslianto, Guslianto; Azis, Nurazmi; Hendri, Jon; Marjulis, Marjulis (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2023)
This research aims to determine the effect of memorizing the Quran on the religious personality of students at Madrasah Aliyah. The method used in this research is a qualitative method with observation and interview techniques. The results obtained in research related to the effects of memorizing the Quran can be seen in the attitudes and behavior of students who are oriented towards religious values, such as the value of istiqomah, the value of morals and manners, the value of faith, and the value of obedience. This effect includes the application of personality values ​​in students' daily lives which can later be emulated by society. Memorizing the Quran is very helpful in encouraging students to become better